Black-Tie Optional Sorites - Teijeiro, Paula (2024)
Sorites is the paradox which exploits the tolerance of vague language to get an absurd conclusion. The present note argues that, contrary to some other approaches, formalizing the antinomy does not serve the purpose of elucidation.